Usable Space Versus Habitat Quality in Forest Management for Bobwhites - Ronald E. Masters; Fred S. Guthery; W. Russ Walsh; Douglass S. Cram; Warren G. Montague (National Quail Symposium Proceedings, 2017)
We determined whether habitat quality (patch richness and diversity, edge density) or the quantity of usable space (suitable permanent cover) best explained the presence or absence of calling male bobwhites (Colinus virginianus) on 50-ha, circular plots (n = 80) in the Ouachita National Forest, Arkansas, during 2000 and 2001. Information theoretic analysis of logistic regression models revealed that usable space was predictive of bobwhite occurrence, whereas habitat quality variables were not. A logistic regression model with data pooled over 2 years predicted the presence of calling males if usable space was >26 ha on the 50-ha plots. Creation of usable space on the study area involved removal of mid story and co-dominant shortleaf pine (Pinus echinata) and hardwoods (wildlife stand improvement = WSI) followed by February or March (late dormant season) prescribed burns at 3-year intervals. Application of WSI and fire results in an understory mosaic of low woody sprouts, forbs, and grasses of varying heights depending on time since the last burn. Our results were consistent with the hypothesis that predicts bobwhite presence as a function of usable space in time versus the classical principle of edge and other habitat quality indicators.
Keywords: Arkansas; Colinus virginianus; edge; habitat quality; northern bobwhite; pine-bluestem; prescribed burning; usable space; wildlife stand improvement